Research portfolio - Gontes, Karolina (Rhodes University, Faculty of Education, Department of Education, 2004)
The purpose of the study is to investigate how mother tongue instruction influences the learner performance in the acquisition of reading and comprehension skills of Khoekhoegowab speaking learners in Grade 2 in comparison with foreign medium of instruction. (p. 1)
Keywords: Curriculum planning -- Namibia; African languages -- Study and teaching -- Namibia; Language and languages -- Study and teaching -- Curricula -- Namibia; Language and education -- Namibia; Language policy -- Namibia; Nama language -- Study and teaching -- Namibia